Aberrant Epstein-Barr virus antibody patterns and chronic lymphocytic leukemia in a Spanish multicentric case-control study - Casabonne, Delphine (Infect Agent Cancer, 2015)
BACKGROUND: Epstein-Barr virus (EBV)-related malignancies harbour distinct serological responses to EBV antigens. We hypothesized that EBV serological patterns can be useful to identify different stages of chronic lymphocytic leukemia. METHODS: Information on 150 cases with chronic lymphocytic leukemia and 157 frequency-matched (by age, sex and region) population-based controls from a Spanish multicentre case-control study was obtained. EBV immunoglobulin G serostatus was evaluated through a peptide-based ELISA and further by immunoblot analysis to EBV early antigens (EA), nuclear antigen (EBNA1), VCA-p18, VCA-p40 and Zebra. Two independent individuals categorized the serological patterns of the western blot analysis. Patients with very high response and diversity in EBV-specific polypeptides, in particular with clear responses to EA-associated proteins, were categorized as having an abnormal reactive pattern (ab_EBV). Adjusted odds ratios (OR) and 95% confidence interval (CI) were estimated using logistic regression models. RESULTS: Almost all subjects were EBV-IgG positive (>95% of cases and controls) whereas ab_EBV patterns were detected in 23% of cases (N = 34) and 11% of controls (N = 17; OR: 2.44, 95% CI, 1.29 to 4.62; P = 0.006), particularly in intermediate/high risk patients. Although based on small numbers, the association was modified by smoking with a gradual reduction of ab_EBV-related OR for all Rai stages from never smokers to current smokers. CONCLUSIONS: Highly distinct EBV antibody diversity patterns revealed by immunoblot analysis were detected in cases compared to controls, detectable at very early stages of the disease and particularly among non smokers. This study provides further evidence of an abnormal immunological response against EBV in patients with chronic lymphocytic leukemia. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/1750-9378-10-5) contains supplementary material, which is available to authorized users.